Attack-related damage of thalamic nuclei in neuromyelitis optica spectrum disorders. Issue 10 (24th May 2019) - Papadopoulou, Athina; Oertel, Frederike Cosima; Gaetano, Laura; Kuchling, Joseph; Zimmermann, Hanna; Chien, Claudia; Siebert, Nadja; Asseyer, Susanna; Bellmann-Strobl, Judith; Ruprecht, Klemens; Chakravarty, M. Mallar; Scheel, Michael; et al.
Abstract : Objectives: In neuromyelitis optica spectrum disorders (NMOSD) thalamic damage is controversial, but thalamic nuclei were never studied separately. We aimed at assessing volume loss of thalamic nuclei in NMOSD. We hypothesised that only specific nuclei are damaged, by attacks affecting structures from which they receive afferences: the lateral geniculate nucleus (LGN), due to optic neuritis (ON) and the ventral posterior nucleus (VPN), due to myelitis. Methods: Thirty-nine patients with aquaporin 4-IgG seropositive NMOSD (age: 50.1±14.1 years, 36 women, 25 with prior ON, 36 with prior myelitis) and 37 healthy controls (age: 47.8 ± 12.5 years, 32 women) were included in this cross-sectional study. Thalamic nuclei were assessed in magnetic resonance images, using a multi-atlas-based approach of automated segmentation. Retinal optical coherence tomography was also performed. Results: Patients with ON showed smaller LGN volumes (181.6±44.2 mm 3 ) compared with controls (198.3±49.4 mm 3 ; B=−16.97, p=0.004) and to patients without ON (206.1±50 mm 3 ; B=−23.74, p=0.001). LGN volume was associated with number of ON episodes (Rho=−0.536, p<0.001), peripapillary retinal nerve fibre layer thickness (B=0.70, p<0.001) and visual function (B=−0.01, p=0.002). Although VPN was not smaller in patients with myelitis (674.3±67.5 mm 3 ) than controls (679.7±68.33; B=−7.36, p=0.594), we found reduced volumes in five patients with combined myelitis and brainstem attacks (B=−76.18, p=0.017). Volumes of entire thalamus and other nuclei were not smaller in patients than controls. Conclusion: These findings suggest attack-related anterograde degeneration rather than diffuse thalamic damage in NMOSD. They also support a potential role of LGN volume as an imaging marker of structural brain damage in these patients.